Polysaccharide Regulation of Intestinal Flora: A Viable Approach to Maintaining Normal Cognitive Performance and Treating Depression - Wang, Xinzhou; Cheng, Lu; Liu, Yanan; Zhang, Ruilin; Wu, Zufang; Weng, Peifang; Zhang, Peng; Zhang, Xin (Frontiers in Microbiology, 2022)
The intestinal tract of a healthy body is home to a large variety and number of microorganisms that will affect every aspect of the host's life. In recent years, polysaccharides have been found to be an important factor affecting intestinal flora. Polysaccharides are widely found in nature and play a key role in the life activities of living organisms. In the intestinal tract of living organisms, polysaccharides have many important functions, such as preventing the imbalance of intestinal flora and maintaining the integrity of the intestinal barrier. Moreover, recent studies suggest that gut microbes can influence brain health through the brain-gut axis. Therefore, maintaining brain health through polysaccharide modulation of gut flora deserves further study. In this review, we outline the mechanisms by which polysaccharides maintain normal intestinal flora structure, as well as improving cognitive function in the brain via the brain-gut axis by virtue of the intestinal flora. We also highlight the important role that gut microbes play in the pathogenesis of depression and the potential for treating depression through the use of polysaccharides to modulate the intestinal flora.